2007
DOI: 10.1289/ehp.9780
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Environmental Tobacco Smoke Potentiates Adult Responses to Allergen in BALB/c Mice

Abstract: BackgroundFetal stress has been linked to adult atherosclerosis, obesity, and diabetes. Epidemiology studies have associated fetal exposure to maternal smoking and postnatal exposure to environmental tobacco smoke (ETS) with increased asthma risk.ObjectiveWe tested the hypothesis, in a mouse model of asthma, that in utero ETS exposure alters airway function and respiratory immune responses in adults.MethodsPregnant Balb/c mice were exposed daily to ETS or HEPA-filtered air (AIR). Offspring inhaled aerosolized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 67 publications
5
79
1
2
Order By: Relevance
“…Several factors have been proposed to contribute to the increasing incidence of asthma and AD [eg, maternal smoking (9), alcohol consumption (10), eating habits (11,12), obesity (13), and work environment (14,15)]. Also maternal stress has been suggested to interfere with fetal immune development (16,17).…”
mentioning
confidence: 99%
“…Several factors have been proposed to contribute to the increasing incidence of asthma and AD [eg, maternal smoking (9), alcohol consumption (10), eating habits (11,12), obesity (13), and work environment (14,15)]. Also maternal stress has been suggested to interfere with fetal immune development (16,17).…”
mentioning
confidence: 99%
“…Both O 3 and diesel exposures increase prostaglandin E 2 (PGE 2 ) levels in the lung fluid of mice (Canning et al, 1991;Ahn et al, 2008), and blocking this activity with indomethacin in the case of O 3 has reversed health effects such as reduced phagocytosis (Canning et al, 1991) and increased susceptibility to infection (Gilmour et al, 1993). However, maternal exposure to cigarette smoke components by inhalation increases allergic sensitization in both experimental animals (Penn et al, 2007;Wu et al, 2009) and in humans (Strachan and Cook, 1998;Gilliland et al, 2006), and this may be due to a different profile of mediators produced in the lung. To better understand how these inhalation exposures to common air pollutants produce contrasting effects through maternal exposure, a comparative study is warranted using the efficient sensitization regimes to identify chemical components and biomarkers that differentially modulate fetal immune development.…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation exposure to environmental or side stream tobacco smoke enhanced the offspring's immune responses to allergen (Penn et al, 2007) and increased lung resistance (Wu et al, 2009). Studies examining prenatal and neonatal inhalation exposures to DE in rats have also shown increases in allergen-specific IgE responses in adults (Watanabe and Ohsawa, 2002).…”
Section: Research Articlementioning
confidence: 99%
“…Prenatal exposure to Environmental Tobacco Smoke (ETS) has been associated with an increased risk of asthma, and during the postnatal period, the exposure increases asthma exacerbations, as well as the risk for respiratory infections (Wang & Pinkerton, 2008). Studies in mice indicate that prenatal exposure to ETS increases allergic responses in postnatal period (Penn et al, 2007;Gern, 2010). The exposure to outdoor pollutants such as Particulate Matter (PM), carbon monoxide (CO), sulphur (SO 2 ), nitrogen (NOx), and ozone, decreases lung function during childhood www.intechopen.com (Mortimer et al, 2008).…”
Section: Lung Development Modifications By Air Pollutantsmentioning
confidence: 99%